Fuzzy Inference System (FIS) dengan Metode Tsukamoto dan Mamdani dalam Menentukan Kelayakan Kenaikan Gaji Karyawan - Akhirina, Tri Yani; Sonny, Michael (Jurnal Komtika (Komputasi dan Informatika), 2017)
Each Company will evaluate the employees by their performance to determine the payroll increase. The payroll increase is a kind of reward from company to the employee’s performance in a year, and this is given once a year. In some respects, the awarding of payroll increase often meets problems, such as the un-objective appraisal and the inappropriate scale amount of increase for it emerges polemic between employees that will give an impact to their performance. To avoid such things, the company needs an appropriate and a flexible method to do the evaluation. The purpose of this research is to implement Fuzzy Inference System (FIS) in determining the employee’s payroll increase feasibility. Logical Fuzzy is a problem completion technique where the membership degree which is commonly represented by the score of 0 and 1, so that it is more balance. One of Fuzzy methods which can be used to solve the problem is Tsukamoto method and Mamdani. Fuzzy Inference System which implements a weighted average to calculate the feasibility of payroll increase is as the final result. The Inference Support System or SPK of the payroll increase feasibility with Tsukamoto method and Mamdani.